Proceeding of the Tenth ACM International Workshop on Vehicular Inter-Networking, Systems, and Applications 2013
DOI: 10.1145/2482967.2482973
|View full text |Cite
|
Sign up to set email alerts
|

Co-existing periodic beaconing and hazard warnings in IEEE 802.11p-based platooning applications

Abstract: A platoon of trucks driving at the same, mutually agreed speed while keeping a minimum inter-vehicle distance will reduce fuel consumption, enhance transport efficiency as well as improve the safety of other adjacent road users. The European profile of IEEE 802.11p for inter-vehicle communications uses a single 10 MHz control channel dedicated to safety-critical data, shared by periodic status updates, CAM (Cooperative Awareness Message), and event-triggered warnings, DENM (Decentralized Environmental Notifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Simulation shown that VeSOMAC can offer better vehicle safety through smaller and bounded packet latency. In [16], the authors evaluated the coexistence of periodic and event-driven data traffic in a safety-critical platooning application. An event-based safety message dissemination strategy was proposed to support vehicle platooning application.…”
Section: Related Workmentioning
confidence: 99%
“…Simulation shown that VeSOMAC can offer better vehicle safety through smaller and bounded packet latency. In [16], the authors evaluated the coexistence of periodic and event-driven data traffic in a safety-critical platooning application. An event-based safety message dissemination strategy was proposed to support vehicle platooning application.…”
Section: Related Workmentioning
confidence: 99%
“…If event-driven messages should co-exist with beacons, the update rate should be as low as possible while still providing enough data to control the process. The beacon update rate should then be adjusted based on the current PER [14].…”
Section: Related Workmentioning
confidence: 99%
“…An overview of information dissemination protocols for VANETs is given in [17]. In [14], the dissemination delay in platooning is considered as a performance measure, i.e., the delay between event detection (e.g., the leading vehicle in the platoon detecting an upcoming traffic jam) and the point in time when the entire platoon successfully received the warning. In order to maintain fuel-efficient inter-vehicle gaps within the platoon while providing the required levels of traffic safety, the need for efficient dissemination strategies of event-driven messages co-existing with high update rate beacons on the same channel emerges.…”
Section: Related Workmentioning
confidence: 99%
“…Kaul et al [9] identifies the age of periodic beacons in vehicular networks as an important performance metric and propose a rate control algorithm to improve its properties. In [10] several information dissemination protocols for VANETs in general are reviewed and in [11], the dissemination delay in platooning is specifically considered. The dissemination delay is defined as the delay between event detection (e.g., the leading vehicle in the platoon detecting an upcoming traffic jam) and the point in time when the entire platoon successfully received the warning.…”
Section: Introductionmentioning
confidence: 99%
“…Different ways of mitigating broadcast storms associated with message dissemination within VANETs have been evaluated in [12] and in [13] where several selective broadcast algorithms are compared from an application perspective using simulations. Co-existence strategies for beacons and event-driven messages are considered in [14] for VANETs in general and in [11,15] for platooning applications. In [15], a combined decentralized/centralized channel access approach is adopted, using real-time schedulability analysis to determine the ratio of bandwidth required for beacons and event-driven messages, respectively.…”
Section: Introductionmentioning
confidence: 99%